ANALISIS PENGEMBANGAN LAHAN UNTUK TANAMAN KACANG TANAH DI JAWA BARAT DARI DATA LANDSAT DENGAN SISTEM INFORMASI GEOGRAFIS - Hidayat, Agus; Adiningsih, Erna Sri; Setiawan, Parwati (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2004)
Land development for peanut plantation is important as one of the efforts to increase peanut production in Indonesia. Land development guidance map that is overlayed with land cover map based on Landsat data can be used as a reference for the implementation. This research was aimed to analyze land development for peanut plantation in West Java based on the existing land suitability map and land cover map from Landsat ETM + in the 2002, and to determine potential areas for peanut plantation based on land suitability and land cover using geographic information system. The result shows that the greater part of the area for peanut plantation in the research area is on the land ranging in low to medium potential although during 3 years (1999-2001) the plant productivity was relatively moderate to high (10,94 - 15,97 kw/ha). Meanwhile, the area that is potential to develop as peanut plantation area in the research area of northern West Java is in Bogor Regenc, particularly around Tinarjaya. The land coverage in the 2002 that was suitable for peanut plantation development area was still shrub (1.201,14 ha), bare land (395,37 ha), rain-fed paddy field (285,75 ha), and dry land (234,63 ha).